A preliminary investigation on the antimicrobial property of neem (Azadirachta indica) leaves. - Sermeno, Ma. Rowena Pasiculan (2002.)
From the Neem (Azadirachta indica) leaf extract. A positive and a negative control were made ready in order to have basis for comparison with the other four Neem leaf concentrations. negative controls were purely sterilized distilled water, while the positive controls used were amoxillin for bacteria and Mycostatin for Candida albicans. The effectivity of these concentrations was tested on the growth of the four selected microorganisms namely: S. epidermidis, S. saprophyticus, Candida albicans, and Microsporum canis did not exhibit any growth and have no significant difference. Neem leaf extract was found completely to inhibit the growth of four organisms at 100 25 060 25 50 50 75 and 100 Four concentrations were prepared (75 and 0 concentration and 75 concentrations showed negative interpretation of inhibitory activity. The lowest concentration inhibited by S. epidermidis and S. saprophyticus was at 25 concentrations. Concentrationns of 100 for Candida albicans. weakly inhibit the growth of S. epidermidis, and S. Saprophyticus. Candida albicans at 25
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Leaves, Neem; Azadirachta indica